Impact of a structured referral algorithm on the ability to monitor adherence to appropriate use criteria for transthoracic echocardiography. Issue 1 (December 2015) - Promislow, Steven; Abunassar, Joseph; Banihashemi, Behnam; Chow, Benjamin; Dwivedi, Girish; Maftoon, Kasra; Burwash, Ian
Abstract Background Many free-form-text referral requisitions for transthoracic echocardiography (TTE) provide insufficient information to adequately evaluate their adherence to Appropriate Use Criteria (AUC). We developed a structured referral requisition algorithm based on requisition deficiencies identified retrospectively in a derivation cohort of 1303 TTE referrals and evaluated the performance of the algorithm in a consecutive series of cardiology outpatient referrals. Methods The validation cohort comprised 286 consecutive TTE outpatient cardiology referrals over a 2-week period. The relevant AUC indication was identified from information extracted from the free-form-text requisition. The structured referral algorithm was applied prospectively to the same cohort using information from the free-form-text requisition, electronic medical record and ordering clinicians. Referrals were classified as appropriate, uncertain, non-adherent (inappropriate) or unclassifiable based on the American College of Cardiology Foundation 2011 AUC. Results Only 28.7 % of free-form-text requisitions provided adequate information to identify the relevant AUC indication, as compared to 94.4 % of referrals using the structured referral algorithm (p  < 0.001). The structured algorithm improved identification in the AUC categories of general evaluation of cardiac structure/function (100 % vs. 43.0 %, p  < 0.001); valvular function (100 % vs. 23.0 %, p  < 0.001); hypertension, heart failure or cardiomyopathy (100 % vs. 20.3 %, p  < 0.001); and adult congenital heart disease (100 % vs. 0 %, p  < 0.001). By applying the algorithm, the number of identifiable non-adherent studies increased from 2.6 to 10.4 % (p <0.001). Conclusions Use of a structured TTE referral algorithm, as opposed to a free-form-text requisition, allowed the vast majority of referrals to be monitored for AUC adherence and facilitated the identification of potentially inappropriate referrals.